Feasibility study and economical evaluations of geothermal heat pumps in Iran. (March 2018) - Yousefi, Hossein; Ármannsson, Halldór; Roumi, Soheil; Tabasi, Sanaz; Mansoori, Hamed; Hosseinzadeh, Mehdi
Highlights: Feasibility of geothermal heat pumps in Iran is evaluated. Economic, energy saving and environmental objective functions are considered. Ambient and soil temperature is absolutely the most important factor and the humidity impact is negligible. In scenario 1, the gas price increased linearly with current trend for next 7 years and Khalkhal is only city where using Heat pump would be economic. In scenario 2, the price of natural gas is assumed to be in global level after 4 years, Mashhad and Qaen also turn out as cost-effective cities for GSHP. Abstract: Negative effects of fossil fuels and the fact that their reserves will be exhausted in the near future have made nations all around the world look for novel replacing technologies. In recent years, the Ground Source Heat Pump (GSHP) has been considered as one of those beneficial solutions in industrial countries. It is obvious that for a replacing technology to be economically favourable is as important as being technically feasible. Iran is a country of several climates and needs to expand its energy basket for development. In this paper, the impact of temperature and humidity variations on the economics of a GSHP system is studied. In order to find the best region to install GSHPs, 9 different areas are selected with respect to ambient temperature and humidity diversity. Then, feasibility studies are carried out using RETScreen software to estimate the profitability of the project. The result indicates that the impact of a humidity variation is negligible in comparison with the temperature variation. Also, to determine the importance of the Iranian government's incentive on the feasibility of GSHP projects, the natural gas price trend is considered in two scenarios. Further, a predicting equation to calculate annual cost based on temperature and a relative cooling/heating load is conducted by a regression method. Finally, the reduction in CO2 emissions due to the possible utilization of a GSHP system is determined in each region.